Pollination on the apple tree IV. Cultivars Willie Sharp, Granny Smith and Delcon - Pasqual, Moacir; Petri, José Luiz; Pereira, Adilson José (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was undertaken in Caçador and Fraiburgo, SC, Brazil in 1978/79 and 1979/80, with pollinations among the following cultivars of apple tree (Malus domestica Bork.): Willie Sharp x (Starkrimson, Delcon, Gala, Blackjon, Golden Delicious, Br-l, Fuji e Mollies delicious); Granny Smith x (Starkrimson, Fuji, Golden Dehicious, Gala e Mollies Delicious); Delcon x (Gala, Starkrimson, Blackjon, Willie Sharp, Golden Delicious, Fuji and Mollies Delicious). A complete randomization with four repetitions and 50 flowers/parcel was used. Self-fertility, parthenocarpy, free pollination, percentage of pollen germination, and the number of anthers and of pollen grains/anther were determined. There was compatibility, in high or low level, among apple tree cvs., with Willie Sharp, Granny Smith and Delcon and all the tested cultivars. The best combinations were: Willie Sharp x Starkrimson, Delcon and Gala; Granny Smith x Starkrimson. Willie Sharp was good pollinator for Starkrimson, Golden Delicious, Br-1 and Fuji; Granny Smith was good pollinator for Fuji, Golden Delicious, Gala and Mollies Delicious; and Delcon was good pollinator for Golden Delicious, Willie and Fuji. Self-fertility and parthenocarpy were insignificant. The three cultivars presented grains of pollen with high germination, but in low number.